Novel optical techniques for contrast enhancement and profilometry of biological and semiconductor samples - Samson, Edward Carlo Copon (Quezon City College of Science, University of the Philippines,c2007.)
This work consist of two parts. In the first part, contrast-enhancement methods (such as dark-field illumination, Rheinberg optical staining, oblique illumination, and polarized-light microscopy) were achieved in a conventional widefield microscope without using any physical filters before the condenser lens that are usually associated with yhese techniques. These methods were attained by replacing the lamp of the microscope with a commercial video projector. The video projector served as source of illumination and it projected images of the necessary filters on the back aperture of the condenser. The use of a projector provides a dynamic and flexible method in shifting from one imaging method to another. Upon evaluation, the constructed optical system has a comparable performance with a conventional dark-field microscope. Finally, optically-stained birefringence imaging was demonstrated with the developed system. Due to the polarization properties of an LCD projector, the system was able to designate structures that are anisotropic and birefringent with a particular color. On the second part, an optical-feedback confocal interferometric microscope was constructed to characterize and analyze a photodiode sample. From the interference image acquired, a high-resolution profile of the surface topography of the photodiode was reconstructed using a phase measurement and extraction method. A 130-nm height difference was measured between the different structures of the sample using this reconstructed surface topography. Generation of heat due to forward-biasing was also detected using the microscope with a measured optical path difference (OPD) of 200 nm. This part of the study provides a high-resolution, non-invasive technique in analyzing and detecting thermal changes in a semiconductor device.
Vita.
Thesis (M.A. Physics)--University of the Philippines Diliman
Keywords: Semiconductors -- Optical properties